Effects of neutron source characteristics in direct and adjoint problems for subcritical systems. (21st December 2006) - Dulla, S.; Cadinu, F.; Picca, P.; Ravetto, P.
The phase space configuration of the neutron source in a subcritical source-driven system has important effects on its physical behaviour. This paper analyses three important aspects: the role of the time and space dispersion of the source neutrons in the simulation of pulsed experiments; the effect of the source characteristics on significant integral parameters for subcritical systems, such as effective multiplication constant and source multiplication; the effect of the choice of the neutron detector (adjoint source) on the neutron importance and, consequently, on integral parameters such as the neutron effective lifetime. The results presented show the importance of a proper treatment of the source phenomena, which always appear relevant.